2010
DOI: 10.1158/1055-9965.epi-10-0658
|View full text |Cite
|
Sign up to set email alerts
|

Do Steroid Hormones Play a Role in the Etiology of Glioma?

Abstract: Gliomas are the most common type of primary malignant brain tumor and have a very poor prognosis. Little is known, however, about the etiology of these tumors. Evidence from a number of sources suggests that endogenous steroid hormones may play a role in the development of gliomas. First, the descriptive epidemiology of glioma suggests a relative protection of females compared with males, particularly during the premenopausal years. Second, some gliomas and glioblastomas express estrogen receptors (ER), especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 80 publications
(118 reference statements)
1
92
0
1
Order By: Relevance
“…A slight male preponderance for brain tumors and specifically medulloblastomas has been previously described (2729), as well as higher reported brain tumor incidence in Sweden than in most other countries in Europe (30) or worldwide (31). These relationships are still not well understood, but the male preponderance may be partly explained by subtype-specific estrogen receptor expression in brain tumors and a protective effect of estradiol compared with testosterone on tumor proliferation (32), whereas ethnic differences may be partly explained by genetic variants that predispose to brain tumors (33). We also found a modest association between high maternal (but not paternal) education level and overall brain tumor risk.…”
Section: Discussionmentioning
confidence: 99%
“…A slight male preponderance for brain tumors and specifically medulloblastomas has been previously described (2729), as well as higher reported brain tumor incidence in Sweden than in most other countries in Europe (30) or worldwide (31). These relationships are still not well understood, but the male preponderance may be partly explained by subtype-specific estrogen receptor expression in brain tumors and a protective effect of estradiol compared with testosterone on tumor proliferation (32), whereas ethnic differences may be partly explained by genetic variants that predispose to brain tumors (33). We also found a modest association between high maternal (but not paternal) education level and overall brain tumor risk.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analyses according to the rs2910164 genotypes suggested an increased mortality in carriers of the variant C allele, a finding largely restricted to females. Although chance may account for these findings, such a result may potentially indicate that expression of the risk-associated variant depends on the hormonal mileau [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Experimental research, in which rats were transplanted with glial tumors, showed a slower rate growth in female rats, a longer survival for females and for the group estrogen treated group (both males and females) (8).…”
Section: Age and Racementioning
confidence: 96%